Development of critical thinking and language proficiency among undergraduate Swedish online EFL students - Johansson, Evelina (Educare, 2022)
Critical thinking (CT) is considered important in second language (L2) learning. Previous studies have investigated and confirmed a correlation between critical thinking and L2 learning in face-to-face (f2f) learning. The present study aimed to investigate the correlation between CT and L2 proficiency in an online learning environment. The participants in this study were undergraduate Swedish students taking part in an online EFL course at a Swedish university. Students’ CT skills were measured by the California Critical Thinking Skills Test (CCTST). As previous studies confirm that vocabulary size correlates with general language proficiency, it was seen as a suitable measure of students’ L2 proficiency. Hence, the Vocabulary Size Test (VST) was used to measure students’ vocabulary size. The present study was designed as a pre-test post-test study aiming to investigate the correlation between the processes of CT development and L2 learning during one semester of four months. Contrary to previous studies, no correlation between CT and L2 proficiency could be detected. Moreover, students in this study made no statistically significant improvement of CT and L2 proficiency. The results must be interpreted in light of students’ already high levels of CT and L2 proficiency and the relatively short testing period.